Single-Stage Fuel Cell to Grid Interface with Multilevel Current-Source Inverters - Cossutta, Pablo Martín (2015)
Renewable energy sources can be used for electric power generation to supply specific devices in distributed systems such as smart grids. Hydrogen fuel cells have proven to be an effective solution to produce electrical energy with fairly good efficiency and minimum environmental pollution. A single-stage solution to interconnect a fuel cell with a low-voltage distribution system is proposed in this paper.The traditional boost dc/dc converter plus voltage source inverter is replaced by a single-stage multilevel current-source inverter (MCSI).The MCSI can both interconnect to the grid and perform the maximum power point tracking algorithm. This novel single-stage converter approach provides active power to the grid, power factor compensation, and reduction of the line current harmonic content.The synchronization, modulation, and control scheme are implemented on a field-programmable gate array board using a fast-prototype high-level synthesis tool to reduce design time. Both simulation and experimental results show excellent behavior and fast dynamics while complying with IEEE and IEC harmonic content regulations.